MANUVER, APLIKASI MONITORING SUMBER DAYA VIRTUAL SERVER DI LINGKUNGAN IoT - Iin Karmila Yusri; Misnawati; Kasim; Andi Rifqial Nur (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The utilization of virtual servers greatly supports the implementation of IoT in integrating many different IoT devices. However, virtual servers often experience interference in terms of their resources . Monitoring the use of virtual server resource capacity must be done to prevent the decline of server services. However, resource monitoring is not enough. There needs to be action during critical conditions of server resources. Virtual server resource management is needed to prevent critical conditions from lasting long and can cause the entire system in the network to go off. This research aims to create a mobile application that can monitor the condition of virtual server resources and also increase the capacity of these resources to prevent servers from going off automatically and manually. This application is built using Proxmox and Nginx. To access the Maneuver application, an internet connection is required. Based on the test results of the Virtual Server Monitoring Application, it is concluded that the Maneuver Application has been successfully made in accordance with the design that has been made. The Maneuver application can monitor the condition of virtual server resources in real-time and the information is displayed in graphical form. The Maneuver application can also add resource capacity manually and automatically